Analisis Penggunaan Model Regresi untuk Prediksi Penjualan Spare Part pada AHASS Nur Andhita Grogol - Hilmi Rezkian Aziz Dama; Ahmad Afif Supianto; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
AHASS Nur Andhita Grogol is one of officially honda's Workshop that located on Nur Andhita Grogol street Depok. so that AHASS can still serve a good service, AHASS need an available spare part stock. however spare part stok usually is not available. while spare part delivery from subsidiary take one to two days. this condition causes provision of service, on AHASS Nur Andhita Grogol is not maximum. therefore to maximalize the provision of service, AHASS need a prediction of spare part sales so that AHASS can make a decision to provide spare part stock in the future. predictions are made on the three most sold spare parts, those are SPX2 Oil, Fluid Injection, and Scooter gear Oil. prediction model were used is polynomial regression third order using data of spare part that sold in maret 2020 until november 2020. prediction on SPX2 Oil generate RMSE value 20.81, on Fluid injection 49,99, and on Scooter gear oil 16.93. prediction results visualized at dashboard form using google data studio platform and usability tested using system usability scale(SUS) which produces a value of 75.00 which is included in the Acceptable category with a rating of